Validation of Cestrum commune (Solanaceae), species from the Sierra Madre del Sur and Trans-Mexican Volcanic Belt, Mexico - Montero Castro, Juan Carlos; Lara-Cabrera, Sabina Irene (Instituto de Ecología, A.C., 2018)
Background and Aims: Cestrum nitidum was described based on herbarium specimens collected by H. Galeotti around Ixtlán de Juárez, Oaxaca, Mexico. Subsequently, this epithet was erroneously used for specimens from the Sierra Madre del Sur and the Trans-Mexican Volcanic Belt. This work clarifies this taxonomic conflict.Methods: A review of literature and herbarium collections (BM, BR, CAS, CIMI, CODAGEM, E, EBUM, ENCB, F, G, GH, IBUG, IEB, K, L, M, MEXU, MICH, NDG, NY, P, PH, QMEX, US) of Cestrum from Mexico was conducted.Key results: The name Cestrum nitidum should only be applied to collections from around Ixtlán de Juárez, Oaxaca, with aromatic and long pedicelled flowers, placed on elongated and lax panicles.Conclusions: Cestrum commune is the correct name for specimens distributed in the Sierra Madre del Sur and the Trans-Mexican Volcanic Belt. Cestrum nitidum must be maintained for specimens from Ixtlán de Juárez, Sierras Orientales Province, Oaxaca.